Fundamental aspects of posture in the context of the spatial organization of the human body - Vypasniak, Ihor; Fedyniak, Nazarii (Journal of Education, Health and Sport, 2021)
Relevance. In a modern society focused on the values ​​of individuality and self-expression, the spatial organization of the body acquires significance as a key characteristic of identity. Its formation is an important indicator of physical health and carries symbolic value. In addition, the spatial organization of the body becomes an integral component of the image, reflecting a person’s ability to effectively present themselves in the social environment. Research tasks. To study the fundamental aspects of posture in the context of the spatial organization of the human body. Research results. The evolution of ideals of female beauty is a constant process that can be traced throughout the history of mankind. These ideals, integrating moral and aesthetic aspects, are reflected in artistic monuments of different eras, serving as historical documents of the cultural canons of female beauty. Today, in connection with the transformations of modern civilization, the phenomenon of the spatial organization of the human body is becoming especially relevant. If earlier the canons of beauty were formed under the influence of art and philosophy, now they are increasingly dependent on medical and social factors, which makes the study of posture as a component of the spatial organization of the body extremely important. Conclusions. The problem of human body asymmetry is the subject of extensive study in scientific literature. It has been found that internal asymmetry of the spatial organization of the body, manifested in uneven distribution of the mass of organs and muscles, is the main factor that leads to the formation of asymmetric postural patterns. Symptoms of musculoskeletal disorders are important warning signals indicating negative changes in the body. One of the main indicators of deterioration of the biomechanics of the musculoskeletal system is destructive changes in the natural curves of the spinal column. These changes lead to increased tension and can cause the development of such pathologies as chronic pain and degeneration of the intervertebral discs.